Comparative Study of Metallocene Modified Gold Nanoparticles Polymer Electrodes for Effective Determination of Dopamine. Issue 12 (30th September 2020) - Atta, Nada F.; Galal, Ahmed; Hassan, Samar H.
Abstract: Here in we present a gold nanoparticles‐poly (3, 4‐ethylenedioxythiophene) (PEDOT) modified with metallocene (ferrocene carboxylic acid (FC1), ferrocene (FC2) or cobaltocene (CC)) composites based electrochemical sensors for sensitive determination of dopamine (DA). Higher electron transfer and electrocatalytic activity towards DA are obtained with FC1. The presence of ferrocenium ions enhances the charge exchange rate and the carboxyl groups enhance the electronic conduction in the composite. DA is determined in presence of uric and ascorbic acids with excellent resolution and sensitivity. DA is determined in urine samples with limit of detection 19.6 nM, in the range of 4 to 160 μM. Abstract :